PENGARUH MICROEXPLOSION TERHADAP KARAKTERISTIK PEMBAKARAN BAHAN BAKAR MINYAK JARAK PAGAR (JATHROPA CURCAS L.) PADA BERBAGAI DIAMETER DROPLET - Rosyadi, Ahmad Adib (ROTOR, 2013)
Insights to develop alternative energy sources comes as the depletion of fossil fuel reserves . One is the use of Jatropha or Jatropha curcas Linnaeus . Plants that can be grown on degraded land and does not require much water and fertilizer proved to be extremely effective if the fruit or seeds developed into biodiesel as an alternative energy to replace diesel oil, fuel oil , even kerosene. Jatropha oil has properties that approach the characteristics of liquid fuel especially diesel oil . This prompted the researchers conducted a study of castor oil to find alternative fuels as a substitute for petroleum. In this study the method used is a true experimental research , by comparing one or more test groups with treatment and without treatment . This study uses a variation of the independent variable droplet diameter to the size of 1.75 mm, 1.88 mm , and 1.98 mm . Dependent variable is the temperature of combustion , burning time , the sound frequency fluctuations and flame visualization The results showed that the larger the droplet diameter greater likelihood microexplosion . From observation of the flame burning with microexplosion found that the larger the droplet diameter , the height and width of the flame will tend to increase. Microexplosion make a bigger flame. Burning castor oil to produce ignition delay time microexplosion sooner. Microexplosion castor oil combustion also generates burning with a good rate . It is approaching the character of diesel oil , the ignition delay time is fast but the diesel combustion temperature is lower than pure castor oil.Â Keywords : microexplosion, burning rate, castor oil